Hydrogen Sulfide Alleviates Alkaline Salt Stress by Regulating the Expression of MicroRNAs in Malus hupehensis Rehd. Roots - Li, Huan; Yu, Ting-Ting; Ning, Yuan-Sheng; Li, Hao; Zhang, Wei-Wei; Yang, Hong-Qiang (Frontiers in Plant Science, 2021)
Malus hupehensis Rehd. var. pingyiensis Jiang (Pingyi Tiancha, PYTC) is an excellent apple rootstock and ornamental tree, but its tolerance to salt stress is weak. Our previous study showed that hydrogen sulfide (H2S) could alleviate damage in M. hupehensis roots under alkaline salt stress. However, the molecular mechanism of H2S mitigation alkaline salt remains to be elucidated. MicroRNAs (miRNAs) play important regulatory roles in plant response to salt stress. Whether miRNAs are involved in the mitigation of alkaline salt stress mediated by H2S remains unclear. In the present study, through the expression analysis of miRNAs and target gene response to H2S and alkaline salt stress in M. hupehensis roots, 115 known miRNAs (belonging to 37 miRNA families) and 15 predicted novel miRNAs were identified. In addition, we identified and analyzed 175 miRNA target genes. We certified the expression levels of 15 miRNAs and nine corresponding target genes by real-time quantitative PCR (qRT-PCR). Interestingly, H2S pretreatment could specifically induce the downregulation of mhp-miR408a expression, and upregulated mhp-miR477a and mhp-miR827. Moreover, root architecture was improved by regulating the expression of mhp-miR159c and mhp-miR169 and their target genes. These results suggest that the miRNA-mediated regulatory network participates in the process of H2S-mitigated alkaline salt stress in M. hupehensis roots. This study provides a further understanding of miRNA regulation in the H2S mitigation of alkaline salt stress in M. hupehensis roots.